Increased positive tree species mixture effects on the abundance and richness of Collembola with stand development in Canadian boreal forests - Yakun Zhang; Sai Peng; Zilong Ma; Chen Chen; Bilei Gao; Xinli Chen; Han Y.H. Chen (Forest Ecosystems)
It is well established that species mixtures could enhance ecosystem functioning in diverse ecosystem types, with these benefits increasing over time. However, the impact of tree mixtures on Collembola communities following stand development in natural forests remains unclear, despite the critical roles Collembola plays in litter decomposition and nutrient cycling. We investigated the effects of tree species mixtures on Collembola abundance, diversity, and community structure by sampling pure and mixed jack pine (Pinus banksiana Lamb.) and trembling aspen (Populus tremuloides Michx.) of 15-year-old and 41-year-old stands in natural boreal forest. In total, 6,620 individuals of Collembola were identified as belonging to 39 species/morphospecies. Our results showed significant effects of stand types on Collembola with higher abundance and richness in conifer and mixed stands than in broadleaf stands. Additionally, with stand development, we observed increased Collembola abundance and richness. In 15-year-old stands, Collembola abundance, richness, and evenness in mixed-species stands were comparable to those in single-species stands. However, as stands developed, tree mixture effects became more pronounced, resulting in higher Collembola abundance and richness in mixed-species stands compared to the average of single-species stands in 41-year-old stands. Further, we observed positive associations between the mixture effects on Collembola abundance and richness with soil nutrient contents. We conclude that tree species mixtures can significantly enhance Collembola abundance and diversity, particularly in older stands and those with elevated soil nutrient levels.